Characterization of the nitrosative status of citrus plants under various abiotic stress conditions - Ziogas, Vasileios; Tanou, Georgia; Filippou, Panagiota S.; Diamantidis, Grigorios; Fotopoulos, Vasileios; Molassiotis, Athanassios (My University, 2011)
Nitric oxide (NO) is a key signaling molecule in plants. However, little is known about the metabolism of endogenous NO in plants under abiotic stress conditions. Using citrus plants (Citrus aurantium L.) exposed to six different abiotic stress conditions (high light intensity, continuous dark, low and high temperature, drought and salinity), several aspects of the NO-related metabolism were investigated. Abiotic stress treatments induced the de novo production of NO in the leaves of plants, particularly in the case of high temperature and high light conditions. Increased NO production was localized in different leaf tissues by confocal laser scanning microscopy using the fluorescent probe 4,5-diaminofluorescin diacetate. Salinity and drought resulted in strong nitrosative DNA damage induced by peroxynitrite, further indicating that abiotic stress situations elicited nitrosative challenges in citrus plants. S-nitroso glutathione reductase (GSNOR) appeared to playa signaling role in the high light, dark and high temperature responses. Protein Tyr-nitration targets were also characterized in leaves of citrus subjected to abiotic stress. Gene expression profiling experiments revealed that a wide array of NO-associated genes in citrus plants (including AOX, XO, GSNO, NOS, NiR and NR) were regulated by abiotic stress conditions. These results indicate that nitrosative responses are key components in the plant's behavior against environmental stimuli and provide further insights into NO-mediated signaling.